The heart of change real-life stories of how people change their organization - Kotter, John P. (Boston Harvard Business School Press, 2002)
Why is change so hard? Because in order to make any transformation successful, you must change more than just the structure and operations of an organization?you need to change people?s behavior. And that is never easy.
Includes index
Keywords: Organizational change